Pengaruh Biaya Produksi dan Penjualan terhadap Laba Bersih pada Rocket Chicken Brebes - Erika Oktavia; Yenny Ernitawati; Azizah Indriyani; Titi Rahmawati; Anggi Ayu Saputra (Universitas Muhadi Setiabudi, 2019)
This study aims to determine and analyze the effect of productional costs and selling on nett income at Rocket Chicken Brebes in year 2018. This research uses secondary data. The population in this study is the annual financial report in period 2018 at Rocket Chicken Brebes. The Samples are 48 data. The Hypothesis testing uses multiple linear regression analysis. The Data analysis uses SPSS 16.0. The results of this study indicate that: 1) the production cost has a significant effect on nett income partially, 2) the selling has a significantly effect on nett income partially and 3) the production costs and sellings have a significant effect on nett income simultaneously.